Building Consumer Trust in Digital Markets: The Role of Sharia-Compliant Business Ethics in Online Transactions - Siti Nurdiana; Halimah; Achmad Basofitrah; Mohammad Dina Afiyah; Muhammad Eka Shaifani (Lembaga Penelitian, Penerbitan dan Pengabdian Kepada Masyarakat Institut Badri Mashduqi, 2025)
This study examines the role of sharia-compliant business ethics in building consumer trust in online transactions in Pasuruan Regency. The study is based on the assumption that consumer trust in digital markets is not determined solely by technological features or transaction efficiency, but is also shaped by the ethical conduct of business actors. Using a qualitative approach with a case study design, this research explores how sharia-compliant ethical principles are practiced in everyday online business activities and how such practices influence consumer trust. Data were collected through in-depth interviews, observation, and documentation involving online sellers, consumers, and other relevant actors in digital transactions. The data were analyzed through data condensation, data display, and conclusion drawing/verification. The findings reveal that honesty in product information, price transparency, clarity of agreement, responsibility in complaint handling, and consistency in service are central elements in fostering consumer trust. These practices reduce uncertainty, create a sense of security, and encourage repeat purchases and long-term customer loyalty. The study further shows that sharia-compliant business ethics functions not only as a moral and religious framework, but also as a strategic intangible resource that supports business sustainability in competitive digital markets. Theoretically, this study contributes to the literature on consumer trust, digital markets, and Islamic business ethics by demonstrating the operational role of ethical values in shaping post-transaction relationships. Practically, the findings suggest that digital business development should integrate ethical commitment alongside technology, marketing, and service innovation. This study highlights the importance of ethics-based digital transactions in strengthening public trust and sustaining local digital market growth.